Analisis Sentimen Ulasan Aplikasi Binar Pada Google Play Store Menggunakan Algoritma Naïve Bayes - Muhammad Raffi; Aries Suharso; Iqbal Maulana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Binar is an online learning platform that provides courses and certifications in the digital field. The Binar app has been downloaded 500,000 times and has a rating of 3.6 on the Google Play Store. However, user ratings sometimes do not match their reviews. In application development, not only the number of ratings but also user opinions need to be considered. Therefore, developers must be able to interpret every opinion given, and sentiment analysis was conducted using the Naïve Bayes Multinomial and Bernoulli algorithms along with Information Gain feature selection to interpret user opinions. This study used the Knowledge Discovery in Database (KDD) method. The data used consisted of 713 reviews of the Binar app, including 518 positive and 195 negative reviews. The best results were obtained in the 9:1 data split scenario with the Bernoulli Naïve Bayes model achieving an accuracy of 93.06%, precision of 87.04%, recall of 100%, f1-score of 93.07%, and AUC of 0.988.